Improved Medical Treatment and Surgical Surveillance of Children and Adolescents with Ulcerative Colitis in the United Kingdom. Issue 7 (13th April 2018) - Auth, Marcus Karl-Keinz; Bunn, Su K; Protheroe, Aimee Leanne; Williams, Linda Jane; Fell, John M; Muhammed, Rafeeq; Croft, Nicholas Michael; Beattie, R Mark; Willmott, Anne; Spray, Christine; Vadamalayan, Babu; Rodrigues, Astor; et al.
Abstract: Background: Pediatric ulcerative colitis (UC) presents at an earlier age and increasing prevalence. Our aim was to examine morbidity, steroid sparing strategies, and surgical outcome in children with active UC. Methods: A national prospective audit was conducted for the inpatient period of all children with UC for medical or surgical treatment in the United Kingdom (UK) over 1 year. Thirty-two participating centers recruited 224 children in 298 admissions, comparisons over 6 years were made with previous audits. Results: Over 6 years, recording of Paediatric Ulcerative Colitis Activity Index (PUCAI) score (median 65)(23% to 55%, P < 0.001), guidelines for acute severe colitis (43% to 77%, P < 0.04), and ileal pouch surgery registration (4% to 56%, P < 0.001) have increased. Corticosteroids were given in 183/298 episodes (61%) with 61/183 (33%) not responding and requiring second line therapy or surgery. Of those treated with anti-TNFalpha (16/61, 26%), 3/16 (18.8%) failed to respond and required colectomy. Prescription of rescue therapy (26% to 49%, P = 0.04) and proportion of anti-TNFalpha (20% to 53%, P = 0.03) had increased, colectomy rate (23.7% to 15%) was not significantly reduced ( P = 0.5). Subtotal colectomy was the most common surgery performed (n = 40), and surgical complications from all procedures occurred in 33%. In 215/224 (96%) iron deficiency anemia was detected and in 51% treated, orally (50.2%) or intravenously (49.8%). Conclusions: A third of children were not responsive to steroids, and a quarter of these were treated with anti-TNFalpha. Colectomy was required in 41/298 (13.7%) of all admissions. Our national audit program indicates effectiveness of actions taken to reduce steroid dependency, surgery, and iron deficiency.